2022
DOI: 10.1155/2022/5208993
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Computed Tomography Scores in Cases of Bronchopulmonary Dysplasia

Abstract: Background. Bronchopulmonary dysplasia (BPD) carries a risk of long-term pulmonary sequelae. High-resolution computed tomography (HRCT) is a method of detecting such structural changes. This study is aimed at characterizing structural abnormalities associated with BPD and at evaluating the clinical findings in the newborn period associated with HRCT scores. Methods. 28 patients born with a mean gestation age of 30 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…The HRCT score was more strongly correlated (r=0.646, p<0.001) with the clinical severity of BPD than the CXR score. In contrast, another study found no significant difference in the mean HRCT scores of moderate and severe BPD [ 118 ]. Moreover, CT scoring systems were directly associated with a variety of adverse physiological and clinical outcomes in neonates with BPD, such as the duration of oxygen exposure, incidence of desaturation events during sleep, severity of wheezing and rate of decline in forced expiratory volume in 1 s [ 119 , 120 ].…”
Section: Radiographical Studiesmentioning
confidence: 98%
“…The HRCT score was more strongly correlated (r=0.646, p<0.001) with the clinical severity of BPD than the CXR score. In contrast, another study found no significant difference in the mean HRCT scores of moderate and severe BPD [ 118 ]. Moreover, CT scoring systems were directly associated with a variety of adverse physiological and clinical outcomes in neonates with BPD, such as the duration of oxygen exposure, incidence of desaturation events during sleep, severity of wheezing and rate of decline in forced expiratory volume in 1 s [ 119 , 120 ].…”
Section: Radiographical Studiesmentioning
confidence: 98%
“…A displasia broncopulmonar possui uma patogênese multifatorial, onde a toxicidade do oxigênio, barotrauma, volutrauma e biotrauma podem estar envolvidos. Sabe-se que a idade gestacional e o peso ao nascer são inversamente proporcionais à frequência de neonatos com DBP e a participação de interleucinas (IL-1β, IL-6 e IL-8) e outros mediadores inflamatórios na etiologia da DBP também é relatada na literatura (Akcan et al, 2022).…”
Section: Histórico E Fisiopatologia Da Displasia Broncopulmonar (Bdp)unclassified